Understanding the growth of black phosphorus crystals. Issue 40 (16th September 2016) - Zhao, Ming; Niu, Xinyue; Guan, Liao; Qian, Haolei; Wang, Wei; Sha, Jian; Wang, Yewu
Abstract : Understanding the growth of black phosphorus crystals. Abstract : The growth of high-quality black phosphorus crystals is very important to further study the physical properties of two-dimensional black phosphorus exfoliated from bulk crystals. Herein, we designed a series of experiments to fully understand the growth of black phosphorus crystals and then explore the roles of metals (or alloys) and I elements in its growth process. Finally, we developed a general approach to grow black phosphorus in high yield with high quality and low cost. The work introduced here sheds light on the growth mechanism of black phosphorus crystals and opens up the possibility of the growth of black phosphorus thin film.